Tesituras sobre la educación de campo y la educación ambiental para valorar el espacio campesino - Marcos Vinícius Guimarães de Paula; Camila Freitas de Santana; Claudia Marcia Lyra Pato (Universidade Federal de Rondônia, 2020)
In this essay, we seek to contribute for a discussion about respect for rural education, with an identification of the field as a political space where social relations take place. Therefore, we present a reflection about the necessity of a public treatment of the rural education, to enable it within a project of emancipatory education that cooperates in the formation of conscious subjects of their place in the world and their rights.  Working side by side, with mobilizing and political veins is the struggle for Environmental Education, which is being established as a process of critical awareness of the world and guarantee the rights of this and future generations. In this sense, the article also addresses environmental education in rural education by defending it to be followed to value the land. We understand that field environmental education will help in the recognition of the field, teaching to care for, protect, and defend the field.